Value-based management in banking: The effects on shareholder returns - Christian Schmaltz; Rainer Lueg; Jesper Agerholm; Kasper Wittrup (International Journal of Business Science and Applied Management, 2020)
In this study, we explore the drivers of total shareholder returns (TSR) in commercial banks, and investigate whether banks subscribing to Value-based Management (VBM) outperform the non-adopters in terms of TSR. We estimate a TSR model using data from 132 listed commercial European and North American banks. First, we demonstrate that banks that have publicly adopted VBM in their operative Management Control Systems (MCS) outperform non-VBM-banks. On average, VBM-adopters generate a 5.8%-points higher annual TSR. They also outperform non-VBM-banks in terms of profitability, growth, and liquidity. Second, we find that banks focus on key performance indicators (KPIs) such as the cost-income ratio, which are sub-optimal indicators of TSR. We suggest the implementation of indicators that are more closely related to TSR, such as return on assets or loan loss provisioning. So far, only a few banks (10%-45%) have considered these KPIs in their MCS. A shift towards our suggested KPIs might even further improve the performance of VBM-adopters. Controlling for macro-economic factors, our findings are stable before and after the financial crisis in 2008.